2019
DOI: 10.1002/tea.21610
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the evidence base for evidence‐based instructional practices in chemistry through meta‐analysis

Abstract: Investigating the effectiveness of instructional practices provides an evidence base to inform instructional decisions. Synthesizing research studies on instructional effectiveness provides an estimate of the generalizability of effectiveness across settings, along with an exploration of factors that may moderate the impact, which cannot be achieved within individual studies. This study sought to provide a synthesis of evidence‐based instructional practices (EBIPs) particular to chemistry through meta‐analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 103 publications
3
61
0
Order By: Relevance
“…, 2013 ), group discussions ( Miller and Tanner, 2015 ), case studies ( Allen and Tanner, 2005 ; Miller and Tanner, 2015 ), and flipped classrooms ( Tucker, 2012 ; van Vliet et al. , 2015 ; Rahman and Lewis, 2020 ), among others, our results add urgency to the need to move beyond coarse categorizations of active learning to more fine-grained work, as it clearly matters to marginalized groups ( Thompson et al. , 2020 ).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…, 2013 ), group discussions ( Miller and Tanner, 2015 ), case studies ( Allen and Tanner, 2005 ; Miller and Tanner, 2015 ), and flipped classrooms ( Tucker, 2012 ; van Vliet et al. , 2015 ; Rahman and Lewis, 2020 ), among others, our results add urgency to the need to move beyond coarse categorizations of active learning to more fine-grained work, as it clearly matters to marginalized groups ( Thompson et al. , 2020 ).…”
Section: Discussionmentioning
confidence: 58%
“…It is used to describe a wide variety of different instructional practices that are infrequently detailed in scholarly publications (Driessen et al, 2020). Although some studies have assessed the effect of specific strategies, such as audience response questions (Caldwell, 2007;Smith et al, 2009;Knight et al, 2013), group discussions (Miller and Tanner, 2015), case studies (Allen and Tanner, 2005;Miller and Tanner, 2015), and flipped classrooms (Tucker, 2012;van Vliet et al, 2015;Rahman and Lewis, 2020), among others, our results add urgency to the need to move beyond coarse categorizations of active learning to more fine-grained work, as it clearly matters to marginalized groups (Thompson et al, 2020). Our research was limited by the publication or instructor descriptions of each course.…”
Section: Limitationsmentioning
confidence: 99%
“…Furthermore, evidence suggests nonlecture teaching methods are more equitable to minoritized and marginalized student groups (Lewis, 2011; Ralph & Lewis, 2020; Shields et al, 2012). These findings have resonated throughout the college STEM community, to the extent that nonlecture teaching methods are often referred to as “evidence‐based instructional practices” or “research‐based instructional strategies” in the literature (Borrego & Henderson, 2014; Gibbons et al, 2018; Landrum et al, 2017; Rahman & Lewis, 2020; Stains & Vickrey, 2017; Van Dusen & Nissen, 2019). Indeed, it is claimed that lecture is “the pedagogical equivalent of bloodletting” because “more effective teaching methods have been overwhelmingly demonstrated” (Wieman, 2014, p. 8320).…”
Section: Introductionmentioning
confidence: 98%
“…Many studies have found that including active learning strategies in the classroom positively impacts student outcomes (e.g., higher exam grades, lower withdrawal rate, etc.) ( 3 , 4 ). However, while including these strategies may increase student performance outcomes, the extent of these benefits may vary in different student populations ( 5 ), and it cannot be assumed that every student in the classroom engages in or benefits from an active learning environment to the same extent ( 6 ).…”
Section: Introductionmentioning
confidence: 99%